Law Enforcement Against Child Perpetrators in the Klitih Phenomenon in the Jurisdiction of the Yogyakarta Special Region Police - Muhammad Enrico Aryaditama; Ikramul Fauzan (Jurnal Kewarganegaraan, 2026)
This empirical juridical research aims to analyze law enforcement, criminological factors, and the obstacles in handling klitih (street violence) cases involving minors within the jurisdiction of the Yogyakarta Regional Police (POLDA DIY). Based on field interview data, it was found that juvenile involvement in klitih is triggered by both internal and external factors. Law enforcement for juvenile offenders is processed through diversion efforts and the juvenile criminal justice system. In its implementation, law enforcement is hampered by a lack of coordination between law enforcement agencies and the community, as well as inadequate public facilities. To address these issues, synergy in supervision between schools and parents, enhanced coordination among authorities, the implementation of legal counseling, and the addition of supporting security facilities—such as CCTV and street lighting—are necessary to assist in case disclosures.